Electrically, Thermally, and Mechanically Anisotropic Gels with a Wide Operational Temperature Range. (16th December 2021) - Tran, Van Tron; Mredha, Md. Tariful Islam; Lee, Yoonseong; Todo, Mitsugu; So, Hongyun; Jeong, Eunju; Park, Woosung; Jeon, Insu
Abstract: Next‐generation applications, such as flexible electronic devices, sensors, actuators, and soft robotics, require anisotropic functional soft materials with controlled, directional electrical and heat conductivities, mechanical properties, and responsiveness, as well as shape‐morphing capability, complex designability, and wide operational temperature ranges. However, a combination of these functions in any single class of materials has been very rarely seen to date. In this study, a novel class of multi‐anisotropic gels is developed to realize all these functions through a new fabrication route. The gels are synthesized by integrating cellulose with poly(3, 4‐ethylenedioxythiophene):poly(styrenesulfonate) (PEDOT:PSS) in tripropylene glycol. The prepared gels exhibit high electrical and thermal conductivities of ≈ 200 S m −1 and ≈ 1.49 W m −1 K −1, respectively, with exceptional Young's modulus (≈ 500 MPa) and tensile strength (≈ 55 MPa), which are much better than the previously reported mechanical properties of PEDOT‐based gels (modulus/strength ≤ 10 MPa). Moreover, the gels exhibit self‐welding ability and maintain their properties for 14 d over a wide temperature range (from − 50 to 35 ° C), covering almost the entire atmospheric temperature range on Earth surface. It is believed that the developed gels are promising candidates for application in many next‐generation flexible devices, some of which are experimentally demonstrated in this study. Abstract : Multi‐anisotropic gels with extraordinary mechanical, electrical, and thermal properties (Young's modulus ≈500 MPa, tensile strength ≈55 MPa, electrical conductivity ≈200 S m −1, and thermal conductivity ≈1.49 W m −1 K −1 ) along with wide temperature range applicability (from −50 to 35 °C) and self‐welding and complex designability are fabricated by rationally integrating cellulose and poly(3, 4‐ethylenedioxythiophene):poly(styrenesulfonate) in tripropylene glycol.